Implementation of Madrasah Principal Supervision Management in Improving The Quality of Learning at Madrasah Aliyah An-Nur Mesuji - Rita Hikmawati; Sunarto, Sunarto; Setiawan, Agus; Hayati, Rina Mida; Choirudin, Choirudin (Revenue Journal: Management and Entrepreneurship, 2025)
This study aims to analyze the implementation of madrasah principal supervision management in improving the quality of learning at Madrasah Aliyah An-Nur Mesuji. The study employed a qualitative approach with field research. Data collection techniques included observation, interviews, and documentation. Data analysis employed data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of madrasah principal supervision management is carried out through four management functions: academic supervision planning, organizing supervision activities, implementing learning supervision, and evaluating and following up on supervision. Programmed supervision can improve teachers' pedagogical competence, lesson planning, teaching methods, and the quality of classroom learning interactions. Obstacles identified included limited supervision time and teacher administrative burdens, but these were overcome through ongoing coaching and a collaborative approach. The study's conclusions indicate that madrasah principal supervision management plays a strategic role in continuously improving the quality of learning.